Effect of Nebulized Morphine on Dyspnea of Mustard Gas-Exposed Patients: A Double-Blind Randomized Clinical Trial Study - Majid Shohrati; Mostafa Ghanei; Asghar Amini Harandi; Soniya Foroghi; Ali Amini Harandi (Pulmonary Medicine)
Background. Dyspnea is one of the main complaints in a group of COPD patients due to exposure to sulfur mustard (SM) and is refractory to conventional therapies. We designed this study to evaluate effectiveness of nebulized morphine in such patients. Materials and Methods. In a double-blind clinical trial study, 40 patients with documented history of exposure to SM were allocated to two groups: group 1 who received 1 mg morphine sulfate diluted by 4 cc normal saline 0.5% using nebulizer once daily for 5 days and group 2 serving as control who received normal saline as placebo. They were visited by pulmonologist 7 times per day to check symptoms and signs and adverse events. Different parameters including patient-scored peak expiratory flow using pick flow meter, visual analogue scale (VAS) for dyspnea, global quality of life and cough, and number of respiratory rate, night time awaking for dyspnea and cough have been assessed. Results. The scores of VAS for dyspnea, cough and quality of life and also respiratory rate, heart rate, and night time awaking due to dyspnea and night time awaking due to cough improved significantly after morphine nebulization without any major adverse events. Also pick expiratory flow has been improved significantly after nebulization in each day. Conclusion. Our results showed the clinical benefit of nebulized morphine on respiratory complaints of patients due to exposure to SM without significant side effects.